Lung-selective 25-hydroxycholesterol nanotherapeutics as a suppressor of COVID-19-associated cytokine storm. (June 2021) - Kim, Hyelim; Lee, Han Sol; Ahn, June Hong; Hong, Kyung Soo; Jang, Jong Geol; An, Jiseon; Mun, Yong-Hyeon; Yoo, So-Yeol; Choi, Yoon Jung; Yun, Mi-Young; Song, Gyu Yong; Joo, Jinmyoung; et al.
Highlights: 25-HC and DDAB nanovesicles (25-HC@DDAB) restore cholesterol levels and effectively suppress cytokine storms. Intravenously administered 25-HC@DDAB exhibits preferential lung tropism and accumulation with high efficiency. 25-HC@DDAB can downregulate NF-κB and SREBP2 signaling pathways in COVID-19 patients' PBMCs, reducing inflammatory cytokine levels. Graphical Abstract: ga1 Abstract: In response to the coronavirus disease-19 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), global efforts are focused on the development of new therapeutic interventions. For the treatment of COVID-19, selective lung-localizing strategies hold tremendous potential, as SARS-CoV-2 invades the lung via ACE2 receptors and causes severe pneumonia. Similarly, recent reports have shown the association of COVID-19 with decreased 25-hydroxycholesterol (25-HC) and increased cytokine levels. This mechanism, which involves the activation of inflammatory NF-κB- and SREBP2-mediated inflammasome signaling pathways, is believed to play a crucial role in COVID-19 pathogenesis, inducing acute respiratory distress syndrome (ARDS) and sepsis. To resolve those clinical conditions observed in severe SARS-CoV-2 patients, we report 25-HC and didodecyldimethylammonium bromide (DDAB) nanovesicles (25-HC@DDAB) as a COVID-19 drug candidate for the restoration of intracellular cholesterol level and suppression of cytokine storm. Our data demonstrate that 25-HC@DDAB can selectively accumulate the lung tissues and effectively downregulate NF-κB and SREBP2 signaling pathways in COVID-19 patient-derived PBMCs, reducing inflammatory cytokine levels. Altogether, our findings suggest that 25-HC@DDAB is a promising candidate for the treatment of symptoms associated with severe COVID-19 patients, such as decreased cholesterol level and cytokine storm.